The Impact of Recycled Neonatal Incubators in Nigeria: A 6-Year Follow-Up Study - Hippolite Onyejiaka Amadi; Jonathan C. Azubuike; Uriah S. Etawo; Uduak R. Offiong; Chinyere Ezeaka; Eyinade Olateju; Gilbert N. Adimora; Akin Osibogun; Ngozi Ibeziako; Edna O. Iroha; Abdulhameed I. Dutse; Christian O. Chukwu; et al. (Hindawi Limited, 2010)
Nigeria has a record of high newborn mortality as an estimated 778 babies die daily, accounting for a ratio of 48 deaths per 1000 live births. The aim of this paper was to show how a deteriorating neonatal delivery system in Nigeria may have, in part, been improved by the application of a novel recycled incubator technique (RIT). Retrospective assessment of clinical, technical, and human factors in 15 Nigerian neonatal centres was carried out to investigate how the application of RIT impacted these factors. Pre-RIT and post-RIT neonatal mortalities were compared by studying case files. Effect on neonatal nursing was studied through questionnaires that were completed by 79 nurses from 9 centres across the country. Technical performance was assessed based on 10-indices scores from clinicians and nurses. The results showed an increase in neonatal survival, nursing enthusiasm, and practice confidence. Appropriately recycled incubators are good substitutes to the less affordable modern incubators in boosting neonatal practice outcome in low-income countries.